Band-selective dynamics in charge-transfer excited iron carbene complexes. (24th April 2019) - Chábera, Pavel; Fredin, Lisa A.; Kjær, Kasper S.; Rosemann, Nils W.; Lindh, Linnea; Prakash, Om; Liu, Yizhu; Wärnmark, Kenneth; Uhlig, Jens; Sundström, Villy; Yartsev, Arkady; Persson, Petter
Abstract : A combination of ultrafast spectroscopy and DFT/TD-DFT calculations of a recently synthesised iron carbene complex elucidates the ultrafast excited state evolution processes in these systems. Abstract : Ultrafast dynamics of photoinduced charge transfer processes in light-harvesting systems based on Earth-abundant transition metal complexes are of current interest for the development of molecular devices for solar energy conversion applications. A combination of ultrafast spectroscopy and first principles quantum chemical calculations of a recently synthesized iron carbene complex is used to elucidate the ultrafast excited state evolution processes in these systems with particular emphasis on investigating the underlying reasons why these complexes show promise in terms of significantly extended lifetimes of charge transfer excited states. Together, our results challenge the traditional excited state landscape for iron-based light harvesting transition metal complexes through radically different ground and excited state properties in alternative oxidation states. This includes intriguing indications of rich band-selective excited state dynamics on ultrafast timescales that are interpreted in terms of excitation energy dependence for excitations into a manifold of charge-transfer states. Some implications of the observed excited state properties and photoinduced dynamics for the utilization of iron carbene complexes for solar energy conversion applications are finally discussed.